L. N. TOLSTOY IN SEARCH OF SPIRITUAL SENSE OF HUMAN - V. E. Gromov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. To turn to the diaries and journalistic works by Leo Tolstoy, to study the content and method of his religious and ethical search. To doubt the faithfulness of his interpretation of the evangelical message of Christ. Theoretical basis. The author proceeded from the necessity of a dialectical understanding of the concepts of nonviolence, mercy, justice and a cultural-historical focus on the possibilities of society in realizing the spirituality principles. Originality. The author focuses on the unilateral nature of the methodology that Leo Tolstoy uses to deny violence, as well as on the ambiguous role of Tolstoy's ideology in the morality of society. Conclusions. The spiritual activities an individual person is able to do and that are instructive for society from the point of view of its moral influence may not be sufficient means for educating moral responsibility in a society as a whole. Tolstoy's methodological approach to justifying the absoluteness of nonviolence principle is one-sided and not productive for a true interpretation of the spiritual nature of the Christ’s message about love and mercy.